2020
DOI: 10.1136/neurintsurg-2019-015764
|View full text |Cite
|
Sign up to set email alerts
|

Transradial approach for neurointerventions: a systematic review of the literature

Abstract: BackgroundDespite the recent increase in the number of publications on diagnostic cerebral angiograms using transradial access (TRA), there have been relatively few regarding TRA for neurointerventional cases. Questions of feasibility and safety may still exist among physicians considering TRA for neurointerventional procedures.MethodsA systematic literature review was performed following PRISMA guidelines. Three online databases (MedLine via PubMed, Scopus and Embase) were searched for articles published betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
68
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 44 publications
1
68
1
Order By: Relevance
“…Mean puncture-to-final angiogram was 62 min in interventional procedures of our study: a recent systematic review (Joshi et al 2020) reported no significant differences in mean access to reperfusion time in patients undergoing mechanical thrombectomy or via TFA or TRA (61.9 vs 61.1 min). TRA may be particularly well suited for stroke patients whose aortic arch anatomy would present a challenge using TFA.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Mean puncture-to-final angiogram was 62 min in interventional procedures of our study: a recent systematic review (Joshi et al 2020) reported no significant differences in mean access to reperfusion time in patients undergoing mechanical thrombectomy or via TFA or TRA (61.9 vs 61.1 min). TRA may be particularly well suited for stroke patients whose aortic arch anatomy would present a challenge using TFA.…”
Section: Discussionmentioning
confidence: 46%
“…The most commonly perceived pitfalls for left transradial access include increased procedural time and operator discomfort (Barros et al 2020). In our sample, left-sided radial access was preferred in posterior circulation or in case of right puncture failure; crossing over the left radial artery may contributed to reduce the number of cases converted in TFA (3,2%) in comparison to other published studies (4,7%-24,8%) (Almallouhi et al 2020;Snelling et al 2018b;Joshi et al 2020). An important aspect of our study was that patients undergone diagnostic DSA were in the outpatient setting, providing advantage in dismission time (allowing the patient to ambulatory immediately after the procedure); it is well-established that observation time after TRA for cerebral angiography is shortened (max.…”
Section: Discussionmentioning
confidence: 65%
“…There is good stability of guiding catheters and less frequent catheter-herniation. A recent systematic review corroborated these advantages and showed excellent procedural success rate with TRA [ 10 ].…”
Section: Discussionmentioning
confidence: 90%
“…Reasons for the discrepancy between the two specialties are the general lack of familiarity of TRA among neuro-interventionalists, the undue concern of vessel injury because of the small caliber of the radial artery, and paucity of publications concerning TRA in neurointerventions. However, several recent neurointerventions are being crossed over to TRA, suggesting this trend may be changing [ 10 ]. However, TRA may pose challenges for using FDDs, especially when it is necessary to use a guide-catheter larger than 6 F. As with every procedure, careful selection of patients and devices will decrease the failure rate as well as complications in TRA.…”
Section: Discussionmentioning
confidence: 99%
“…In a systemic review of the literature of transradial approach for neurointervention in 1,342 cases, complications related to the radial approach was classified into minor (asymptomatic and found on routine follow-up or minimally symptomatic, not requiring readmission and intervention) and major (symptomatic and require further intervention). There were two patients (0.15%) with a major complication, one patient of symptomatic radial artery occlusion, one patient of large hematoma requiring transfusion, and 37 patients (2.75%) with minor complications, including 27 patients of asymptomatic RAO, severe radial artery spasm in four patients, and small forearm hematoma in six patients [9]. Allen's test is crucial before transradial approach to prevent major complications of symptomatic RAO.…”
Section: Discussionmentioning
confidence: 99%